If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -9x = 2x + -7 Reorder the terms: 15 + -9x = -7 + 2x Solving 15 + -9x = -7 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 15 + -9x + -2x = -7 + 2x + -2x Combine like terms: -9x + -2x = -11x 15 + -11x = -7 + 2x + -2x Combine like terms: 2x + -2x = 0 15 + -11x = -7 + 0 15 + -11x = -7 Add '-15' to each side of the equation. 15 + -15 + -11x = -7 + -15 Combine like terms: 15 + -15 = 0 0 + -11x = -7 + -15 -11x = -7 + -15 Combine like terms: -7 + -15 = -22 -11x = -22 Divide each side by '-11'. x = 2 Simplifying x = 2
| 3x^2-5x+2y-4=0 | | 3y/6 | | (-5)-(-8)-4y+(-4x)-(-7y)-(-10x)= | | 77+5(x+9)=x | | 9x-(-7y)-(-6)+9-(-2x)-4y= | | (-x)-(-6)+(-4x)+(-7y)-1-8y= | | (-8)+(-8x)+(-y)+4+(-x)+(-9y)= | | -4a^3*2b^2= | | (-8y)-1+y+(-x)-3x-(-8)= | | 10x^24=56 | | 6x-293=6x-13 | | 3y+4+6x-3x-2y-2= | | 10y-6x+4-4x+6y-6= | | 5y-2y+5x+4x-7+9= | | b*c*d*c= | | 3y-1-2y-2x+8-4x= | | a*b*-3*-3= | | 64-6x=8-10x | | p*6*q*-1= | | -3*n*2*m= | | -2*4*m*m= | | y=x^2+(m-1)x+4 | | c*c*3*b= | | 4*a*b*4= | | m*2*n*3= | | c*c*c= | | b+4/4-b-10/2 | | b*b*a= | | 48x^2-8x^3=0 | | 7y^2-7y-15=0 | | 41-7x=2x+21 | | 6-9x=78-38x |